2007
DOI: 10.1111/j.1444-2906.2007.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of wild pearl oysters Pinctada fucata, Pinctada margaritifera and Pinctada sugillata (Bivalvia: Pteriidae) in Taiwan

Abstract: In order to understand growth features of pearl oysters in the genus Pinctada, i.e. Pinctada fucata, Pinctada margaritifera, and Pinctada sugillata in Taiwan, a total of 3062 wild individuals of these species from juvenile to adult were collected monthly from March 2001 to April 2002 in Jukeng, Pingtung County, south-west Taiwan. Quantitative measurements of live oysters were conducted for shell height (SH), shell length (SL), shell width (SW), hinge length (HL), and wet weight (WW). Different cohorts were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The comparison of the relationship SW-SH investigated during this study with that of other species belonging to the same genus from different areas showed that P. radiata in Monastir (E2) has a higher SW increase against SH than those of P. fucata (Gould, 1850), P. margaritifera (L., 1758) and P. sugillata (Reeve, 1857) in Taiwan (Hwang et al 2007), Korea (Shimizu 1999) and Japan (Wada 1984). Furthermore, it is worth noting that the variable SW was also considered as the most important morphological character in the aquaculture of other pearl oyster species; e.g., P. fucata, P. margaritifera and P. sugillata since it greatly affects the number and size of the inserted pearl nuclei (Hwang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of the relationship SW-SH investigated during this study with that of other species belonging to the same genus from different areas showed that P. radiata in Monastir (E2) has a higher SW increase against SH than those of P. fucata (Gould, 1850), P. margaritifera (L., 1758) and P. sugillata (Reeve, 1857) in Taiwan (Hwang et al 2007), Korea (Shimizu 1999) and Japan (Wada 1984). Furthermore, it is worth noting that the variable SW was also considered as the most important morphological character in the aquaculture of other pearl oyster species; e.g., P. fucata, P. margaritifera and P. sugillata since it greatly affects the number and size of the inserted pearl nuclei (Hwang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is worth noting that the variable SW was also considered as the most important morphological character in the aquaculture of other pearl oyster species; e.g., P. fucata, P. margaritifera and P. sugillata since it greatly affects the number and size of the inserted pearl nuclei (Hwang et al 2007). These differences could be in relation to environmental and therefore nutritional factors or to genetic ones as was reported for P. fucata populations in Japan (Wada 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In general, SH of small oysters grows faster than large ones and juveniles faster than adults. Studies on pearl oyster P. martensii (Xie et al 1984, Komaru & Wada, 1994, Mohamed et al 2006, Hwang et al 2007) proved that growth of shell length decreases with age. The increase of shell length in the first year is the fastest, and slows down in the following years, which is also confirmed in the present study.…”
Section: Factors Affecting Growthmentioning
confidence: 97%
“…From June 2003to March 2005, 100 oysters were randomly collected at monthly intervals, cleaned and shell height (SH ± 0.01 mm) and total weight (TW ± 0.01 g) were measured (Hwang et al 2007). …”
Section: Measurementmentioning
confidence: 99%
“…PCA Six variables (SH: shell height; SL: shell length; SW: shell width; HL: hinge length; Hpn: height of the nacreous part; Lpn: length of the nacreous part) were measured to the nearest 0.01 mm using digital calipers (Guanglu TM ) ( Figure 2). All measurements were done on the left valve (Huang and Okutani, 2003;Hwang et al, 2007;Tlig-Zouari et al, 2010). All morphological variables were transformed through dividing by the average (A) of SL, SH, and SW to remove the effects of size.…”
Section: Samplingmentioning
confidence: 99%